Analysis of Indonesian Spelling Errors Differences Among Students Based on Their Regional Dialects at Al Razi Sinar Harapan Junior High School - Sijabat, Josafat; Tamba, Ester Maesya; Bintang, Andreas; Syakilla, Maysha (Indonesian Journal of Interdisciplinary Research in Science and Technology, 2024)
This study aims to analyze the differences in Indonesian spelling errors among students based on their regional dialects at Al Razi Sinar Harapan  Junior High School. The research method employed is a combination of qualitative and quantitative approaches involving interviews with Indonesian language teachers and questionnaires distributed to students. The findings indicate variations in spelling errors among students from different regions, as well as the influence of regional dialects on spelling error patterns. Additionally, the impact of social media and technology contributes to students' spelling errors. This research provides a deeper understanding of the factors affecting Indonesian spelling errors among students.